Beyond forgiveness and suicidal behaviour in adolescence: the moderating role of gender - Quintana-Orts, Cirenia Luz; Mérida-López, Sergio; Rey-Peña, Lourdes (My University, 2017)
With the development of positive psychology, forgiveness has received increasing attention among psychologists from different social science fields . Empirical evidences have suggested associations between forgiveness and suicidal ideation and behaviours, but moderator’s role of gender has been scarcely studied. The aim of the present study was to test the role of gender as a potential moderating factor in the relationship between forgiveness and suicidal behaviour in adolescence. A total of 586 Spanish adolescents from three different high school centres took part in this study. Their average age was 15.51 (SD= 1.17) and 51.2% were men. We conducted moderation analyses and used age and personality factors as control variables. First, we found negative association between forgiveness and risk suicide. Moreover, results showed that gender moderated the relationship between forgiveness and suicidal ideation. Specifically, males compared to females were found to show significantly higher tendency of suicidal behaviour depending on their level of forgiveness. Thus, males who showed higher scores on forgiveness tend to report lower levels of suicidal behaviour, whereas males who reported lower scores on forgiveness showed greater levels of risk suicide. Our findings suggest that forgiveness may operate as a key buffering factor against suicidal risk underlying the importance of examining gender differences in this association. These findings provide therapeutic targets to reduce risk of suicide in this high-risk group of adolescent males with lower levels of forgiveness. Our results are discussed in terms of the need of using gender perspectives in positive psychology intervention programs.
Keywords: Adolescencia; Suicidio; Forgiveness; Suicida behaviour; Adolescence